2017
DOI: 10.18632/oncotarget.20203
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of genetic polymorphisms in genes of base excision repair pathway on the efficacy and acute toxicities of (chemo)radiotherapy in patients with nasopharyngeal carcinoma

Abstract: PurposeTo explore whether polymorphisms in base excision repair (BER) pathway genes are predictors of (chemo)radiotherapy outcome in patients with nasopharyngeal carcinoma (NPC).MethodsWe genotyped five potentially functional single nucleotide polymorphisms (SNPs) of three genes in the BER pathway in 174 NPC patients who were treated with (chemo)radiotherapy. Sequenom MassArray was used for SNPs analysis. The efficacy at the end of radiotherapy and at 3 months after radiotherapy was evaluated by Response Evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Most of them evaluated the associations by adopting the strategy of candidate genes. Those candidate genes and pathways include DNA damage and repair involved in doublestrand breaks repair genes [26] and the base excision repair pathway [27]. Other important cellular signaling pathways include the Wnt/β-catenin pathway [28], cell cycle regulated genes, the NF-κB pathways [29], angiogenesis-related genes [30], and GAS5 lncRNAs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them evaluated the associations by adopting the strategy of candidate genes. Those candidate genes and pathways include DNA damage and repair involved in doublestrand breaks repair genes [26] and the base excision repair pathway [27]. Other important cellular signaling pathways include the Wnt/β-catenin pathway [28], cell cycle regulated genes, the NF-κB pathways [29], angiogenesis-related genes [30], and GAS5 lncRNAs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in XRCC1-194 and XRCC1-399 are also related to the risk of NSCLC [18]. Wang et al [19] have reported that the presence of XRCC1 rs25489 had a significant impact on primary tumor efficacy at the end of radiotherapy and may act as a biomarker for the curative effect of radiotherapy. Zhai et al [20] found that patients with nasopharyngeal carcinoma (NPC) carrying the XRCC1 codon 399 Gln/Gln genotype had a higher rate of tumor regression after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] The difference of clinical response and outcome on NPC suggests the inter-individual variation might play a more important role in NPC susceptibility, [ 4 ] especially the ability of DNA damage repair. [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%